A JOURNEY OF RESILIENT FARMERS IN CHIBOMBO, ZAMBIA: A story of how Caroline Mwanza and Joseph Sibanda reimagined their future - Kasoma-Pele, Winnie; Jacobs-Mata, I.; Mutenje, M. (2025)
In the heart of Chibombo District, where frequent droughts and unpredictable rains have long threatened the survival of smallholder farmers, AICCRA Zambia and its partners are working to flip the script by empowering smallholder farmers with climate-smart agricultural innovations and services that strengthen resilience, productivity, and livelihoods.